Síntese e caracterização de pós de Li2TiSiO5 e Na2TiSiO5 - Albarici, Viviane Cristina (Universidade Federal de São Carlos, 2004)
This work presents a systematic study of the synthesis and characterization of Li2TiSiO5 and Na2TiSiO5 compounds. We studied their structural, morphologic and luminescent properties using X ray diffraction, Raman spectroscopy and scanning electron microscopy. These materials have in their crystalline structures centers of pentacoordinated titanium. The samples were produced through two different synthetic routes, both based on Pechini method. Different heat treatments were applied in order to obtain crystalline and disordered materials. The polymeric resins obtained were submitted to Raman spectroscopy, to verify their influence on the different routes used in the powders preparation. These materials were analyzed by X ray diffraction and Raman spectroscopy, to study the thermal evolution of the phases, as well as the structural disorder of the samples. Rietveld refinement were performed on the diffraction patterns of the crystalline samples. The morphology of the samples was investigated by scanning electron microscopy. After structural characterization, luminescent properties of the synthesized powders were studied. These studies were realized using excitation wavelengths of 250 and 488nm. The obtained results showed that Li2TiSiO5 did not present luminescent properties when the excitement wavelength was 250nm but they did when disordered and excited by the 488nm line. On the other hand Na2TiSiO5 samples presented luminescence with excitement of 250nm although didn t present this property when excited with 488nm. For a better understanding of the luminescent properties in the Li2TiSiO5 and Na2TiSiO5 compounds, their electronic structures were investigated by quantum-mechanical studies. This investigation allowed us obtain information about the effects of deformations in the crystalline structure and in the physical properties of these compounds. The obtained results suggest that the luminescent properties can occur by different mechanisms and thus depend on the crystalline structure and the excitement wavelength.
Synthesis and characterization of powers of Li2TiSiO5 and Na2TiSiO5
Keywords: Semicondutores; Método de Pechini; Luminescência; Pó de cerâmica - síntese; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA